Pelatihan Kader Sehat Jiwa dengan Pendekatan Terapi SEFT sebagai Upaya Tanggap Bencana - Kustiawan, Ridwan; Somantri, Iwan; Cahyati, Peni; Indriyani, Novi; Adini, Syaukia (Jurnal Abdimas Kesehatan (JAK), 2025)
The prevalence of mental disorders in Tasikmalaya City continues to increase, based on the results of a preliminary study that the number of patients with mental disorders registered at the Tamansari Health Center is 60 people, while data on risk disorders and mentally healthy communities is not yet available. Therefore, the community service team will train mentally healthy cadres to be able to identify through early detection of mental health problems, provide mental health counseling and be able to apply SEFT therapy so that the community can maintain their health. This community service activity is a training activity for 30 mentally healthy cadres, with the material provided being early detection of mental health problems and mental health counseling activities as well as training cadres with SEFT therapy as an independent disaster response effort. with lecture methods, questions and answers, and role play. The activity was carried out in a series of community service programs for the IPTEKS for the community (IbM) Tasikmalaya Health Polytechnic. The activity was carried out in June-November 2024. The results of the training showed that the cadre's knowledge score about early detection and community mental health counseling techniques increased by 12.2 points compared to before. Statistically, using the Wilcoxon test, the results showed a difference in the average knowledge score before and after training, with a significance level of ρ = 0.0001 (ρ <0.05). It is expected that after being given training, the posyandu cadres will contribute to increasing community knowledge about mental health through counseling activities, providing guidance and monitoring to families who have family members with mental disorders and can apply SEFT therapy to people who experience psychosocial disorders. The conclusion is that there is an increase in the knowledge of mental health cadres after being given training